A Short Apocalyptic Text Based on the Prophecy of Ezra (Esdras Salathiel) - Haile, Getatchew (Aethiopica, 2018)
The main themes of the text, occasionally ascribed to Ezra (Salathiel), are the Second Coming of Jesus Christ, the end of the world, the future rulers of Ethiopia, and the honouring of the Sabbaths. It is cast in the spirit of 4 Ezra, quoting it and Jubilees occasionally and extensively. As in 4 Ezra, its author is interested in knowing and declaring the future to call the faithful to observe the law and the ordinances. Reckoning the time by cycles, aqmar, provides him the revelation of future events ‘with exact dates’. The text, composed before the sixteenth century, is one more source of Gǝʿǝz apocalyptic literature. The article is an edition and translation of it as preserved in EMML 6429, fols 9v–39r.